Coupling toxicokinetic–toxicodynamic and population models for assessing aquatic ecological risks to time‐varying pesticide exposures. (6th August 2018) - Thursby, Glen; Sappington, Keith; Etterson, Matthew
Abstract: Population modeling evaluations of pesticide exposure time series were compared with aspects of a currently used risk assessment process. The US Environmental Protection Agency's Office of Pesticide Programs models daily aquatic 30‐yr pesticide exposure distributions in its risk assessments, but does not routinely make full use of the information in such time series. We used mysid shrimp Americamysis bahia toxicity and demographic data to demonstrate the value of a toxicokinetic–toxicodynamic model coupled with a series of matrix population models in risk assessment refinements. This species is a small epibenthic marine crustacean routinely used in regulatory toxicity tests. We demonstrate how the model coupling can refine current risk assessments using only existing standard regulatory toxicity test results. Several exposure scenarios (each with the same initial risk characterization as determined by a more traditional organism‐based approach) were created within which population modeling documented risks different from those of assessments based on the traditional approach. We also present different acute and chronic toxicity data scenarios by which toxicokinetic–toxicodynamic coupled with population modeling can distinguish responses that traditional risk evaluations are not designed to detect. Our results reinforce the benefits of this type of modeling in risk evaluations, especially related to time‐varying exposure concentrations. Environ Toxicol Chem 2018;37:2633–2644. Published 2018 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.